2021
DOI: 10.1002/fsh.10621
|View full text |Cite
|
Sign up to set email alerts
|

Relative Cost and Post‐Release Performance of Hatchery Catchable Rainbow Trout Grown to Two Target Sizes

Abstract: Catchable-sized hatchery trout (hereafter, catchables) have become a staple component of many fisheries management programs throughout North America. Due to their size, catchables create immediate fisheries once they are stocked, and fisheries managers have gradually shifted towards stocking fewer, larger trout. However, the cost of growing larger fish may reduce the efficiencies of catchable stocking programs overall. We grew catchable-sized Rainbow Trout Oncorhynchus mykiss to two target average sizes (254 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
(60 reference statements)
1
7
0
Order By: Relevance
“…We found that stocking age-2 June sucker produced 65 times more recruits at a given investment (cost) than stocking age-1 individuals. This result is congruent with other cost benefit analyses for stocked fishes, which have shown distinct advantages for stocking larger fish (Wiley et al 1993;Eggold and Horms 2001;Branigan et al 2021). Although it is more expensive to raise June sucker to age-2, it appears that the survival advantage conferred by additional rearing time significantly outweighs the elevated cost, perhaps by reducing susceptibility to predation.…”
Section: Discussionsupporting
confidence: 90%
“…We found that stocking age-2 June sucker produced 65 times more recruits at a given investment (cost) than stocking age-1 individuals. This result is congruent with other cost benefit analyses for stocked fishes, which have shown distinct advantages for stocking larger fish (Wiley et al 1993;Eggold and Horms 2001;Branigan et al 2021). Although it is more expensive to raise June sucker to age-2, it appears that the survival advantage conferred by additional rearing time significantly outweighs the elevated cost, perhaps by reducing susceptibility to predation.…”
Section: Discussionsupporting
confidence: 90%
“…Previous research from put‐and‐take trout fisheries has demonstrated a positive effect of fish length on return‐to‐creel rates (Cassinelli and Meyer 2018; Branigan et al. 2021) and angler satisfaction (Birdsong et al. 2021).…”
Section: Discussionmentioning
confidence: 98%
“…However, rearing of hatchery fish to catchable size is expensive, so efficiently allocating hatchery resources for optimal angler use and satisfaction is important (Branigan et al. 2021). Fisheries managers are therefore faced with decisions about stocking density, stocking frequency, and fish size.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment of survival of stocked Rainbow Trout may aid in further refining the timing and amount of stocking needed to sustain the population at a desired abundance. Further, assessing the influence of stocking fewer but perhaps larger (in terms of mean length) Rainbow Trout to meet management goals may be warranted (Branigan et al 2021). Spatial variation in abundance of Brown Trout could be used to direct harvest rates along the river as angling pressure has historically not been distributed evenly along the Greers Ferry tailwater (Bowman et al 1994).…”
Section: Discussionmentioning
confidence: 99%